The Development and Evaluation of A Multiplex Real-Time PCR Assay for the Detection of ESBL Genes in Urinary Tract Infections - Ruth Reid; Shivanthi Samaras (International Journal of Clinical Microbiology, 2018)
Background Overuse of beta-lactam antibiotics has lead to selection for extended-spectrum β-lactamase (ESBL) producing Enterobacteriaceae, a major cause of antibiotic resistant urinary tract infections (UTIs). Standard detection methods are time-consuming, with disputed accuracy. This study describes a novel real-time PCR method to detect CTX-M, SHV, OXA and TEM. Methods 179 Enterobacteriaceae isolates from UTIs were collected from the Leicester Royal Infirmary, UK. A multiplex Plexor®-based real-time PCR assay detected ESBLs using their specific amplicon melting temperature, during each cycle, removing the need for a melt-curve analysis. Validation was achieved by end-point PCR and disk diffusion. Results The method was able to produce rapid and accurate results, achieving a sensitivity and specificity of 94.9% and 72% respectively, and the assay can differentiate between the different ESBL genes, with ease. Conclusions With further investigation, a Plexor®-based assay could form the basis of a high-throughput kit that health services could use to detect ESBLs or other antibiotic resistance genes.
Keywords: Extended-spectrum beta-lactamases